Analysis of the Use of Standard and Nonstandard Words on Banners in Pekanbaru City, Bina Widya District - Setiawati, Sonia; Pratiwi, Eka Setia; Faizah, Hasnah (FKIP - Universitas Riau, 2025)
As the national language, Indonesian has rules and norms that must be followed, including the use of standard words in public media such as banners. However, in practice, many errors are still found in the use of words that do not conform to the Enhanced Spelling System (Ejaan yang Disempurnakan, EYD). This study aims to analyze the types of errors in the use of standard and nonstandard words on banners in Pekanbaru City, particularly in the Bina Widya District. This research employs a qualitative descriptive method using documentation and note-taking techniques. Data were collected by photographing and recording word errors on banners scattered throughout the research area and then analyzed based on the language rules outlined in the Kamus Besar Bahasa Indonesia (KBBI). The results of the study show that a significant number of nonstandard words are still found on banners, including errors in writing, spelling, and capitalization. A total of 18 nonstandard words were identified from 13 banners observed. These findings indicate that the public’s understanding of proper and correct use of the Indonesian language remains low. This study is expected to raise public awareness of the importance of using Indonesian accurately in public information media.